Preconception Profile of Children Aged 5-6 Years in Understanding the Concept of Pattern Recognition - Wizaroh Putri; Ifa Aristia Sandra Ekayati (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2026)
The ability to recognize patterns is a crucial aspect of early childhood cognitive development, as it plays a role in building logical thinking skills, problem-solving abilities, and mathematics learning readiness for the subsequent stages. However, children's initial capability to understand the concept of pattern recognition still exhibits variations, thereby requiring the identification of children's preconceptions before providing a more targeted learning stimulation. This study aims to describe the preconception profile of children aged 5–6 years in understanding the concept of pattern recognition. This study utilizes a quantitative approach with a descriptive quantitative research design. The research subjects consisted of 18 children aged 5–6 years at TK Retno Asih, who were selected using a total sampling technique so that all children in group B were included as research samples. Data collection was conducted through a checklist observation sheet that had been validated by two expert lecturers. The results showed that the preconception profile of children aged 5–6 years regarding the concept of pattern recognition is still at the early developmental stage. The indicator for the ability to verbally state pattern sequences showed the highest achievement, while the ability to create patterns independently obtained the lowest achievement. These findings indicate that children's initial ability to understand the concept of pattern recognition still requires learning stimulation that is concrete, structured, and aligned with the cognitive developmental characteristics of early childhood.